Selling coffin and other funeral services / Shirley Angie Sitimin... [et al.] - Sitimin, Shirley Angie; Martin, Avitus Adrian; Dyadmus, Joegeoffrey; W Dabbi, Maxwell Richard (Faculty of Administration Science & Policy Studies, 2006)
Funeral services nowadays become more and more important as it will make the funeral arrangements the death easier and well planned. Due this fact, this business plan is come up to fill the needs and requirement of the entrepreneur and other people which are interested in this business. This business is focuses more on providing and offering good services and variety of coffins. Blacksmith Undertaker Services is located in the area of Putatan. The business is located in our own land. The strategic and ideal location of the business become the customer's attraction and well known in the area. Which were located nearby Penampang, Papar and Kata kinabalu. This location has a complete infrastructure such as water, electricity and telephone line.